Financial Literacy Training for Mushrooms Business Development in Sitio Tamale, The Philippines - Kenny Fernando; Andrey Hasiholan Pulungan; Budi Kurniawan; Elfina Astrela Sambuaga; Victoria Del Gracia Matahelumual; Yolanda Rian Wiratam; Claudia Jessica Tunadi (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
A business really needs adequate records to evaluate business operational activities and also determine future improvement steps. 30 Youths in Sitio Tamale, The Philippines have developed a Mushroom Business business which took place in October 2021. The Research Team was entrusted with providing training virtually to answer the need for mushroom Business development in the village. This study aims to describe how virtual training could be effectively conducted by employing modules and virtual presentation. We used SPSS 22.0 to statistically analyze and to describe its percentages based on LikertScale (1-5) questionnaires about topic relevance, modules quality, duration, and understanding. The results shows that 66.67% agree this financial feasibility is relevant. The printed modules are considered as the best way for 53.55% as they strongly agree. However, the one-day training is not sufficient as only 13.33% strongly agree. Lastly, the two-time translation during presentation made 60% participants do not comprehensively understand.